Population-based study of intra-household gender differences in water insecurity: reliability and validity of a survey instrument for use in rural Uganda - Tsai, Alexander C.; Kakuhikire, Bernard; Mushavi, Rumbidzai; Vořechovská, Dagmar; Perkins, Jessica M.; McDonough, Amy Q.; Bangsberg, David R. (Journal of water and health, 2016)
Hundreds of millions of people worldwide lack adequate access to water. Water insecurity, which is defined as having limited or uncertain availability of safe water or the ability to acquire safe water in socially acceptable ways, is typically overlooked by development organizations focusing on water availability. To address the urgent need in the literature for validated measures of water insecurity, we conducted a population-based study in rural Uganda with 327 reproductive-age women and 204 linked men from the same households. We used a novel method of photo identification so that we could accurately elicit study participants’ primary household water sources, thereby enabling us to identify water sources for objective water quality testing and distance/elevation measurement. Our psychometric analyses provided strong evidence of the internal structure, reliability, and validity of a new eight-item Household Water Insecurity Access Scale (HWIAS). Important intra-household gender differences in perceptions of water insecurity were observed, with men generally perceiving household water insecurity as being less severe compared to women. In summary, the HWIAS represents a reliable and valid measure of water insecurity, particularly among women, and may be useful for informing and evaluating interventions to improve water access in resource-limited settings
Keywords: Gender; Uganda; water insecurity